Concepts Joy and Suffering in Russian Linguaculture (Proceedings of Southern Federal University. Philology, 2017)
Svetlana V. Korostova (Rostov-on-Don, Russian Federation)In the Russian linguistic consciousness, the concepts of emotions joy and suffering are verbalized at the lexical and phraseological levels, forming the basis for metaphorical combinations.Concepts of emotions, suffering and joy are mutually reinforcing: in the presupposition of the idea of suffering, there is a knowledge that it is not infinite and is always replaced by joy. Russian naive-linguistic consciousness reflects the oldest ideas about the alternation of phenomena and events, desirable and undesirable for man. The concepts of suffering and joy are closely related to the universal category of time. As observations on linguistic projections of concepts show, suffering is realized as a longer process than joy.Emotives of different levels of language represent emotional states of joy and suffering in Russian linguistic culture. According to the National Corpus of the Russian language, lexical demonstrators of the concept of joy dominate. Cognitive interpretation of events in the mind of a person can be changed under the influence of the emotional regime carried out by the media.Key words: conceptualization of emotions, cognitive interpretation of events, emotive, emotional regime.DOI 10.23683/1995-0640-2017-4-88-96  Quote:Korostova, S. V. (2017). Concepts Joy and Suffering in Russian Linguaculture. Proceedings of Southern federal university. Philology. 4, 88‒96.